Clarifying the prospective relationships between social anxiety and eating disorder symptoms and underlying vulnerabilities. (1st December 2016) - Levinson, Cheri A.; Rodebaugh, Thomas L.
Abstract: Social anxiety and eating disorders are highly comorbid. Several explanations for these high levels of comorbidity have been theorized. First, social anxiety might be a vulnerability factor for eating disorders. Second, eating disorders might be a vulnerability factor for social anxiety. Third, the two kinds of disorders may have common, shared psychological vulnerabilities. The current study ( N = 300 undergraduate women) investigates a model of social anxiety and eating disorder symptoms that examines each of these possibilities across two time points (Time 1 and six months later). We do not find support for either social anxiety or eating disorder symptoms per se predicting each other across time. Instead, we find that some underlying vulnerabilities prospectively predict symptoms of both disorders, whereas other vulnerabilities are specific to symptoms of one disorder. Specifically we find that maladaptive perfectionism is a shared prospective vulnerability for social anxiety and eating disorder symptoms. Alternatively, we find that social appearance anxiety is specific for eating disorder symptoms, whereas high standards is specific for social anxiety symptoms. These data help clarify our understanding of how and why social anxiety and eating disorder symptoms frequently co-occur.